(untitled) (Bangladesh Journal of Pharmacology, 2017)
Clinical trials evaluating the safety and efficacy of daclatasvir for chronic hepatitis C virus (HCV) genotype 4 infection are scarce and yet with small sample sizes. Therefore, we conducted this systematic review to investigate the efficacy of daclatasvir in HCV genotype 4 treatment. A computer literature search of PubMed, Scopus, Embase, Ovid, Web of knowledge, and Cochrane central was conducted. We selected studies comparing daclatasvir plus peginterferon-alfa/ribavirin versus placebo plus peginterferon-alfa/ribavirin in patients with HCV genotype 4 infection. Pooling data from two randomized controlled trials (n = 154 patients) showed that daclatasvir/peg-interferon/ribavirin treatment achieved a moderate sustained virologic response rate of 76% after 12 weeks and of 79% after 24 weeks. The daclatasvir containing regimen was superior to the placebo containing regimen in terms of virologic response rates after 12 weeks (RR=1.9% CI 1.3 to 2.6) and 24 weeks (RR=1.8% CI 1.3 to 2.5). More effective regimens are needed for HCV genotype 4.